Advancements in the Diagnosis and Management of Chronic Rhinosinusitis with Nasal Polyps: A Clinical and Molecular Perspective - Boyarovich, Yusupov Abdullo; Mavlonovich, Yuldoshev Abdurahmon (Journal of Science in Medicine and Life, 2025)
Chronic rhinosinusitis with nasal polyps (CRSwNP) remains a significant burden in otorhinolaryngology due to its complex pathophysiology and high recurrence rates. This article explores the latest diagnostic modalities and therapeutic strategies, including endoscopic techniques, biologic therapies, and immunologic insights. A comprehensive review of recent molecular and cellular discoveries highlights novel biomarkers and immunophenotyping applications. The study incorporates multicenter clinical data, evaluates outcomes of surgical and medical interventions, and presents a predictive model for disease recurrence based on histopathological and cytokine profiles. These findings pave the way for personalized medicine in CRSwNP and offer practical guidelines for clinicians.